(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The MSMEs (Micro, Small and Medium Enterprises) face several problems in their day-to-day operations and overall functioning, like in production and marketing of their products. It is difficult for them to sell their output at remunerative prices and cannot spend much on advertising, marketing research, etc. They also face stiff competition from large firms. Inadequate infrastructural facilities and access to credit are other major problems. The MSMEs also find it difficult to recruit and motivate skilled managerial and technical personnel. They are mainly reluctant to adopt modern. A prominent drawback of the MSME sector is that a predominant number (94%) of the enterprises are in the unorganized sector. Due to this, there is lack of reliability and hampers monitoring of development initiatives and formulation of appropriate schemes to meet the differential needs of the heterogeneous profile of the enterprises. The MSMEs in Arunachal are not enjoying any better policies instead of having such resources and talents. The major problems faced by MSMEs of this region are lack of access to equity and credit. This sector also has poor paying capacity and therefore faces shortage of skilled manpower resulting in absence of managerial capabilities, marketing channels and brand building capacity. The Sector faces a number of problems - absence of adequate and timely banking finance, limited capital and knowledge, non-availability, identification of new markets, constraints on modernsation & expansions, non availability of highly skilled labour at affordable cost, follow up with various government agencies to resolve problems etc.